2015
DOI: 10.1590/1808-1657000482013
|View full text |Cite
|
Sign up to set email alerts
|

Fungicidal activity and constituents of Ageratum conyzoides essential oil from three regions in São Paulo state, Brazil

Abstract: The chemical composition and antifungal activity of the Ageratum conyzoidesessential oils, obtained from the leaves collected in Ibiúna (1), Ribeirão Pires (2) and Campinas (3) in the São Paulo state, Brazil, were investigated. The essential oils were obtained from A. conyzoidesleaves by hydrodestilation and analyzed by GC/MS. The chemical composition of the A. conyzoides oil collected in Ribeirão Pires and Ibiúna consisted mainly of precocene I and II. The essential oil from leaves collected in Campinas had o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, they have low molecular weight and lipophilic properties that allows them to easily penetrate cell membrane [ 28 ] causing irreversible cell wall damage and cellular organelle as well as affecting the pH homeostasis and equilibrium of inorganic ions [ 29 , 30 , 31 ]. Another study on the mode of action of E.Os on fungal growth suggested that A. conyzoides E.O was able to cross the plasma membrane of A. flavus and interact with the membrane structures of cytoplasmic organelles thus preventing the fungal growth [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they have low molecular weight and lipophilic properties that allows them to easily penetrate cell membrane [ 28 ] causing irreversible cell wall damage and cellular organelle as well as affecting the pH homeostasis and equilibrium of inorganic ions [ 29 , 30 , 31 ]. Another study on the mode of action of E.Os on fungal growth suggested that A. conyzoides E.O was able to cross the plasma membrane of A. flavus and interact with the membrane structures of cytoplasmic organelles thus preventing the fungal growth [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…33,54,55 whereas the bioactivity of A. conyzoides is thought to hinge on the compounds precorenes I and II. 57,57 The better inhibition and reduction of the incidence, development and spread of the leaf and stem blight by H. suaveolens over the other plant extracts in this study may have been due to higher presence of these phytochemical compound in it than in the other test plants. This finding of fungitoxic activities of the test extracts is consistent with 46 and 58 where aqueous leaf extract of S. jamaicensis and A. conyzoides inhibited F. oxysporum, P. corylophilum, A. sclerotiorum.and Botryodiplodia theobromae by 80.74-100%.…”
Section: Resultsmentioning
confidence: 70%
“…As expected, similar composition showed similar activity because biological performance is correlated with the existence of secondary metabolites. This hypothesis was later confirmed by Esper et al [94] when investigation was carried out about the variation in chemical composition and antifungal effect of the essential oils obtained from three different locations (Ribeirão Pires, Ibiúna, and Campinas) of São Paulo state, Brazil. Precocene I and II were in higher proportions in the oil from Ribeirão Pires (1) and Ibiúna (2), while in the essential oil obtained from the leaves collected from Campinas (3), precocene I, (E)-caryophyllene, and α-humulene were in highest ratio as compared with traces of precocene II.…”
Section: Ageratum Conyzoides Against Fungal Genus Aspergillusmentioning
confidence: 58%